Perangkat Lunak Logistik Kemanusiaan untuk Memantau Distribusi Bantuan Korban Bencana Alam - Efraim Owen Gunawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2020)
Regional Warehouse of the Indonesian Red Cross Regional Gresik houses and handles the humanitarian logistical assistance process in East Java, Sulawesi and throughout Eastern Indonesia. Humanitarian logistical assistance is an emergency item that can be distributed when disaster strikes. Currently, in carrying out the logistics process applications are used that are embedded on the local machine. Now, the application is out to date and can not perform some functions according to the needs of the warehouse so that some processes are done manually using spreedsheet. Confirmation of receipt and delivery is also still often done via whatsapp messager so that errors often occur. Besides, giving track numbers are not unique, so that items are difficult to track. This causes the logistics process in the warehouse to be effective less, so we need an online software that can facilitate the logistics process. The Software developed is a web-based logistics assistance system. This system also adapted to the results of the analysis of existing applications with several additional features to adjust the needs of the warehouse. The web system was developed using serverside PHP programming language 7.12.13 with Laravel Framework 5.7 and also several libraries that support clienside css, javascript like bootstrap or jQuery. The final result of the software development contains movement of goods that occur in the warehouse, such as input of goods entering and leaving, as well as by renewal the tracking number and assigning the tracking number automatically to the each of relief item.